Participation of Glutamatergic Ionotropic Receptors in Excitotoxicity: The Neuroprotective Role of Prolactin. (1st May 2021) - Rodriguez-Chavez, V.; Moran, J.; Molina-Salinas, G.; Zepeda Ruiz, W.A.; Rodriguez, M.C.; Picazo, O.; Cerbon, M.
Highlights: Glutamate overstimulation induces excitotoxicity and neuronal cell death. Excitotoxicity is involved in several neurological and neurodegenerative diseases. Advances have been made in the knowledge of neuroprotection against excitotoxicity. Prolactin is promising hormone for neuroprotection against excitotoxicity. Abstract: Glutamate (Glu) is known as the main excitatory neurotransmitter in the central nervous system. It can trigger a series of processes ranging from synaptic plasticity to neurophysiological regulation. To carry out its functions, Glu acts via interaction with its cognate receptors, which are ligand-dependent. Glutamatergic receptors include ionotropic and metabotropic categories. The first allows the passage of ions through the postsynaptic membrane, while the metabotropic subtype activates signaling cascades through second messengers. It is well known that an excess of extracellular Glu concentration induces overstimulation of ionotropic glutamatergic receptors (iGluRs), causing the excitotoxicity phenomenon that leads to neuronal damage and cell death. Excitotoxicity plays a crucial role in different brain pathologies such as brain strokes, epilepsy and neurodegenerative disorders. However, until now, there are no effective neuroprotective compounds to prevent or rescue neurons from excitotoxicity. Thus, the continuous elucidation of the molecular mechanisms underlying excitotoxicity in order to prevent damage or neuronal death is necessary. Therefore, the aim of this review was to summarize the current knowledge regarding iGluRs, while describing their structures and molecular mechanisms of action, including their role in excitotoxicity, as well as the current strategies to reduce excitotoxic damage. Particularly, strategies mediated by prolactin, a somatotropin family-related hormone that displays a significant neuroprotective effect against both Glu and kainic acid-induced excitotoxicity in the hippocampus, are described. Finally, the role of prolactin as a possible molecule in the treatment of excitotoxicity in neurological diseases is discussed.